2016
DOI: 10.1007/s10461-016-1362-5
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Patterns of HIV-Infected Russian Women with and Without Hepatitis C Virus Co-infection

Abstract: Individuals with HIV and hepatitis C virus (HCV) co-infection may experience substance use related health complications. This study characterized substance use patterns between HIV/HCV co-infected and HIV mono-infected Russian women. HIV-infected women (N = 247; M age = 30.0) in St. Petersburg, Russia, completed a survey assessing substance use, problematic substance use, and the co-occurrence of substance use and sexual behaviors. Covariate adjusted logistic and linear regression analyses indicated that HIV/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…Participants were HIV-infected young women ( N = 250 at baseline; N = 217 at three-month follow-up) receiving HIV medical care in a comprehensive HIV care center in Saint Petersburg, Russia (see 50 for more details). Given the focus on PEth and self-reported alcohol use, analyses are limited to participants with non-missing PEth and self-reported alcohol use scores at both baseline and follow-up ( N = 204; 81.6% of the baseline sample; 42 missing on both variables; 3 missing on PEth only; 1 missing on self-reported alcohol only; underreporting at baseline among the full sample did not significantly predict study attrition, and median level of baseline PEth did not significantly differ between study attriters and those who remained in the study).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were HIV-infected young women ( N = 250 at baseline; N = 217 at three-month follow-up) receiving HIV medical care in a comprehensive HIV care center in Saint Petersburg, Russia (see 50 for more details). Given the focus on PEth and self-reported alcohol use, analyses are limited to participants with non-missing PEth and self-reported alcohol use scores at both baseline and follow-up ( N = 204; 81.6% of the baseline sample; 42 missing on both variables; 3 missing on PEth only; 1 missing on self-reported alcohol only; underreporting at baseline among the full sample did not significantly predict study attrition, and median level of baseline PEth did not significantly differ between study attriters and those who remained in the study).…”
Section: Methodsmentioning
confidence: 99%
“…36 There is high prevalence of HCV infection among Russian PLWH. 4 The current study includes women seeking HIV care at two clinical care sites: the [redacted] and the [redacted]. Both sites offer comprehensive HIV care, including mental health care, for HIV-infected women.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…3 Among HIV-infected women in Saint Petersburg, Russia, a study by our group observed that 57.1% were HCV co-infected. 4 Behaviors related to injection drug use, such as needle sharing, have contributed to the rapid spread of HIV/HCV co-infection among PWID globally, 5 including in Saint Petersburg, Russia. [6][7][8] Alcohol use poses a marked and persistent health threat to women living with HIV/HCV co-infection.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%
“…В таблицах приведены вероятные причины и пути их преодоления, где качественная терапия с современными лекарственными препаратами является наиболее значимой для ЛЖВ [10]. Летальные случаи в первые недели и месяцы с начала АРВТ относятся чаще всего к развитию синдрома восстановления иммунной системы (СВИС), где непосредственными причинами смерти могут быть обострение или возникновение ВИЧ-ассоциированных заболеваний, диссеминирование туберкулеза и других микобактериозов [12,16,[20][21][22]. В историях болезни диагноз СВИС выставляется достаточно редко из-за отсутствия лабораторной верификации, поскольку сложно обеспечить динамическое определение РНК ВИЧ и CD4-лимфоцитов.…”
unclassified